Variation of total serum cholesterol among the patient with thyroid dysfunction - Risal, P; Maharjan, BR; Koju, R; Makaju, RK; Gautem, M (Kathmandu University Medical Journal, 2010)
Background: Thyroid hormone has its effect in the lipid metabolism. Thus, thyroid disorder is usually associated with the dyslipidaemia. Hypercholesterolemia is an established risk factor for the cardiovascular disease (CVD) and therefore in case of overt hypothyroidism which is associated with hypercholesterolemia, CVD is most likely to occur. Objectives: controversies still persist about the hypercholesterolemia and sub clinical hypothyroidism. Hence, we conducted our study to elucidate the relation of thyroid hormone with cholesterol in different thyroid disorder. Material and Method: All patients suspected of thyroid disorder within a period of one year were included in the study and free thyroxine-3 (fT3), free thyroxine-4 fT4, Thyroid Stimulating Hormone (TSH) and total cholesterol (TC) in the serum were estimated. Statistical analysis was carried out by using SPSS. 13. Results: Among the 169 cases, 32.5% of the patients were having thyroid disorder. In which 8.3% were of hypothyroid, 7.1% were of sub clinical hypothyroid, 8.3% were of hyperthyroid, 7.7% were of sub clinical hyperthyroid and 1.2% cases were of pan hypothyroid. We observed significant negative correlation between TC & fT3(r = -0.226, p = 0.003), significant negative correlation between total cholesterol & fT4(r = -0.197, p = 0.010) and significant positive correlation between TC & TSH(r = 0.365, p = 0.000). Total cholesterol was significantly raised in hypothyroidism (Mean ±SD 283±53, p = 0.000) in comparison to euthyroid population (mean ±SD, 195±58). But cholesterol was not significantly increased in sub clinical hypothyroidism (mean ±SD, 240±46) Conclusion: Our results show that total cholesterol level in serum is affected by the blood thyroid hormone level. Therefore, screening for hypercholesterolemia could be useful in patients with hypothyroidism to reduce associated disease. Key words: Thyroid hormone; Cholesterol; Nepal DOI: 10.3126/kumj.v8i2.3573 Kathmandu University Medical Journal (2010), Vol. 8, No. 2, Issue 30, 265-268